Accelerating Human Evolution by Theosophical Initiation Annie Besant's Pedagogy and the Creation of Benares Hindu University - Mühlematter, Yves (Okkulte Moderne, 2022)
The main subjects of analysis in the present book are the stages of initiation in the grand scheme of Theosophical evolution. Mühlematter shows that the stages of initiation were the blueprint for Annie Besant's pedagogy, which she implemented in the Central Hindu College in Benares. In doing so, he succeeds in making intelligible how "esoteric" knowledge was transferred to public institutions and how a broader public could be reached as a result.